Taxa de geração de resíduos da construção civil em edificações na cidade de João Pessoa - Costa, Ricardo Vasconcelos Gomes da (2012)
Given the high index of construction in the city of João Pessoa, in northeast Brazil and the frequent irregular disposal of its residues, the objective of this work was to study the generation rate of construction wastes (CW) based on constructed area of the building, so that a more effective inspection can be implemented by the proper instances. A sample of building was choose among those under construction in João Pessoa and the collection of data regarding to their CW volume generated and other characteristics of the building were performed. From the volume of CW discharged by the building companies, the generation rate was calculated based on a unit mass of 1.025 kg/m³ determined in this work. The sample was divided into two groups: (1) control group and (2) non-control group. The control group was made up by the building in which the author worked as inspector, visiting them on a daily base. Analysis of variance showed that the generation rate from control group did not differ from that from non-control group, showing that the methodology applied for data collection can be considered a valid one. Results showed that the generation rate of class A (CONAMA Resolution 307) CW in João Pessoa is 86,27 kg/m² and that there were no significant difference between that from dwellings and non-dwellings buildings. The 90% confidence interval for the arithmetic mean was calculated and the lower and upper limits were 62,31 and 136,02 kg/m², respectively. Based on these results the control on the generation and disposal of CW can be done more efficiently by municipal authorities.